The Relationship between Murottal Therapy and Pain Quality in College Students with Musculoskeletal Pain in 2019 - Thyra Annisaa Putri; Aulia Chairani; Riezky Valentina (Talenta Publisher, 2020)
ABSTRACT Musculoskeletal pain is often called as musculoskeletal disorder (MSDs). One of the most common causes of musculoskeletal pain is occupational-related causes. Musculoskeletal pain is often experienced by college students. The factors that influence the occurrence of musculoskeletal pain in college students are learning activities as well as static body positions/posture while studying. This causes discomfort in learning activities for college students. This study aims to determine the relationship/correlation between the administration of murottal therapy and the quality of musculoskeletal pain in 2016 class Medical Faculty students of UPN (FK UPN). This research type is semi-experimental using a cohort study design. The sampling technique uses purposive sampling. The research sample used was 68 people. The data was collected at the Medical Faculty of UPN ‘Veteran’ Jakarta using a research instrument in the form of a Nordic Musculoskeletal Questionnaire (NMQ) and measured by the Numeric Rating Scale (NRS) pain scale. The results indicated that 30 students (44.1%) had mild pain, 37 (55.4%) had moderate pain, 1 (1.5%) had severe pain respectively before murottal therapy is given. The results of bivariate analysis using the Wilcoxon test indicated that there was a relationship between murottal therapy and the quality of musculoskeletal pain in 2016 class Medical Faculty students of UPN (p = 0.000). The easy and inexpensive therapy of pain management is necessary such as through the administration of murottal therapy for 15 minutes. Keywords: Musculoskeletal Disorders, Pain, Murottal Therapy ABSTRAK Nyeri muskuloskeletal sering disebut gangguan muskuloskeletal.Salah satu penyebab terseringnya nyeri muskuloskeletal adalah karena pekerjaan. Nyeri muskuloskeletal seringkali dialami oleh mahasiswa. Faktor-faktor yang berpengaruh pada kejadian nyeri muskuloskeletal pada mahasiswa adalah kegiatan belajar mengajar serta posisi tubuh statis saat belajar. Hal ini menyebabkan ketidaknyamanan dalam kegiatan belajar mengajar pada mahasiswa.Penelitian ini bertujuan untuk mengetahui hubungan antara pemberian terapi murottal dengan kualitas nyeri muskuloskeletal pada mahasiswa FK UPN angkatan 2016.Jenis penelitian ini semi-eksperimetal dengan desain penelitian kohort.Teknik pengambilan sampel menggunakan purposive sampling. Sampel penelitian yang digunakan sebanyak 68 orang. Pengambilan data dilakukan di Fakultas Kedokteran UPN ‘Veteran’ Jakarta menggunakan instrumen penelitian berupa kuesioner Nordic Musculoskeletal Questionnaire (NMQ) dandiukur dengan skala nyeri Numeric Rating Scale (NRS). Hasil penelitian menunjukkan mahasiswa dengan nyeri ringan sebanyak 30 orang (44,1%), 37 orang nyeri sedang (55,4), 1 orang mengalami nyeri berat (1,5%) sebelum diberikan terapi murottal. Hasil analisis bivariat dengan uji Wilcoxon menunjukkan terdapat hubungan antara terapi murottal dengan kualitas nyeri muskuloskeletal pada mahasiswa FK UPN angkatan 2016 (p=0,000). Manajemen penanganan nyeri dengan terapi yang mudah dan murah diperlukan seperti pemberian terapi murottal selama 15 menit. Kata Kunci: Gangguan Muskuloskeletal, Nyeri, Terapi Murottal